Multilateral finance and development - Wolfgang König (Intereconomics, 1975)
This article presents an outline of major international financial institutions, i.e. the Bretton Woods organisations. The focus of analysis is on the conceptions that have shaped the posture of these institutions on development issues and on their corresponding activities and problems.
Keywords: 330; Financing